(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
This article aims to advance a demonstration that management tools such as Strategic Planning (SP) and the Balanced Scorecard (BSC) are the right tools that improve the quality of service across business units, academic and administrative institutions of a public university. The PE makes the vision, mission, objectives and strategies of the organization, which is essential to develop a model of leadership and management as the CMI. The latter allows you to measure, communicate and operationalize the strategic plan based on four (4) perspective, read: Company, Financial, Internal Processes and Organisational Learning and Development, through the identification of stakeholders that mostly influence the extent of goals and objectives. This paper presents an empirical case in the Department of Management and General Studies Agroindustrial Engineering Program, University Lisandro Alvarado (UCLA). In conclusion, the study shows the deployment of the strategy set by UCLA, through the CMI to design an academic unit, and how their teachers focuses on key elements in achieving those goals, and boost the real changes that the university requires to respond to their environment.